The Integration of the Direct and Indirect Methods in Lichenometry for Dating Buddhist Sacred Walls in Langtang Valley, Nepal Himalaya. Issue 1 (1st February 2016) - Emerman, Steven H.; Adhikari, Santosh; Panday, Suman; Bhattarai, Tara N.; Gautam, Tara; Fellows, Steven A.; Anderson, Ryan B.; Adhikari, Narayan; Karki, Kabita; Palmer, Mallory A.
ABSTRACT: Buddhist sacred walls, called mani walls, are common between Langtang Village and Kyanjin Gompa in Langtang Valley, Nepal Himalaya. The objective of this study was to interview local informants about the mani wall traditions and to use lichenometry to resolve discrepancies regarding the maintenance of the mani walls. The maximum diameters of the lichen Rhizocarpon geographicum were measured on each of 24 mani walls. An apparent lichen growth curve was developed using five sources of indirect data, including the foundation of one stupa (sacred monument) and two locations of former ice cover, for which ages were obtained from local informants, and two debris ridges that had been dated by 10 Be. The direct method was pursued by measuring the maximum diameters of 20 lichens in remote locations in both 2009 and 2014. Based on the indirect method, the mani walls are cleaned on a geometric mean cycle time of 13 years. The direct and indirect methods yield equivalent ages when the minimum direct growth rate (geometric mean divided by geometric standard deviation) is used for older ages (>400 years), while the maximum direct growth rate (geometric mean multiplied by geometric standard deviation) is used for younger ages (<50 years).